Impact of Paracoccus sp. EGY7 carotenoids on triple-negative breast cancer cells: invitro study - Karim Abdelazim; Ahmed Hussein; Sherine N. Khattab; Shaymaa Essam El Feky; Nehad Noby (AMB Express, 2025)
Abstract This study investigates the effect of Paracoccus sp. EGY7 carotenoids on the triple-negative breast cancer cell line (MDA-MB-231). The bacterial strain was isolated, and its carotenoids profile was analyzed via HPLC-DAD-MS. Cytotoxicity, migration tests and the expression of BAX and BCL-2 at the gene and protein levels were carried out to evaluate the therapeutic efficiency of the produced carotenoids. Molecular docking analysis estimated the binding affinity between zeaxanthin and BCL-2 protein. Chromatographic analysis revealed zeaxanthin as the major carotenoid (48.3%). The extract exhibited significant cytotoxicity against MDA-MB-231 cells with an IC50 of 1200 µg. It notably reduced cell migration, with wound closure percentages of 37.50% and 79.17% for the 600 µg group, while the percentages were 12.50% and 53.50% for the 1200 µg group, compared to 71.67% and 95.67% for the control at 24 and 48 h post-treatment, respectively. The extract induced apoptosis, as evidenced by significantly increased BAX/BCL-2 gene expression ratios at 600 and 1200 µg (p < 0.05). Western blotting showed increased BAX protein expression at 600 and 1200 µg compared to the control group (p < 0.001), and significantly lower BCL-2 protein expression (p = 0.000005 for 1200 µg and p = 0.0001 for 600 µg). Docking analysis indicated a strong affinity of zeaxanthin to BCL-2 (ΔG = -9.773241 kcal/mol) compared to obatoclax (ΔG = -7.419345 kcal/mol). Paracoccus sp. EGY7 carotenoids are a promising anticancer agent against MDA-MB-231 cells. They effectively promote apoptosis and prevent metastasis, crucial for disease advancement in cancer cells.